Location of a constriction in the lumen of a transmembrane pore by targeted covalent attachment of polymer molecules. - Movileanu, L; Cheley, S; Howorka, S; Braha, O; Bayley, H (2001)
Few methods exist for obtaining the internal dimensions of transmembrane pores for which 3-D structures are lacking or for showing that structures determined by crystallography reflect the internal dimensions of pores in lipid bilayers. Several approaches, involving polymer penetration and transport, have revealed limiting diameters for various pores. But, in general, these approaches do not indicate the locations of constrictions in the channel lumen. Here, we combine cysteine mutagenesis and chemical modification with sulfhydryl-reactive polymers to locate the constriction in the lumen of the staphylococcal alpha-hemolysin pore, a model protein of known structure. The rates of reaction of each of four polymeric reagents (MePEG-OPSS) of different masses towards individual single cysteine mutants, comprising a set with cysteines distributed over the length of the lumen of the pore, were determined by macroscopic current recording. The rates for the three larger polymers (1.8, 2.5, and 5.0 kD) were normalized with respect to the rates of reaction with a 1.0-kD polymer for each of the seven positions in the lumen. The rate of reaction of the 5.0-kD polymer dropped dramatically at the centrally located Cys-111 residue and positions distal to Cys-111, whether the reagent was applied from the trans or the cis side of the bilayer. This semi-quantitative analysis sufficed to demonstrate that a constriction is located at the midpoint of the pore lumen, as predicted by the crystal structure, and although the constriction allows a 2.5-kD polymer to pass, transport of a 5.0-kD molecule is greatly restricted. In addition, PEG chains gave greater reductions in pore conductance when covalently attached to the narrower regions of the lumen, permitting further definition of the interior of the pore. The procedures described here should be applicable to other pores and to related structures such as the vestibules of ion channels.